What can wages and employment tell us about the UK's productivity puzzle? - Richard Blundell; Claire Crawford; Claire Wenchao Michelle Jin Crawford (Institute for Fiscal Studies (IFS), 2013)
This paper uses individual data on employment and wages to shed light on the UK's productivity puzzle. It finds that workforce composition cannot explain the reduction in wages and hence productivity that we observe; instead, real wages have fallen significantly within jobs. Why? One possibility we investigate is higher labour supply in this recession than in the past. Another is lower trade union membership. Alternatively, it might be driven by a fall in productivity as a result of a lower capital-labour ratio. We cannot tell whether productivity is driving wages or vice versa, but understanding why wages have fallen within jobs is at the heart of the UK's productivity puzzle.
Keywords: J01; J21; 330; productivity; employment; wages; recession